A common oxytocin receptor gene (OXTR) polymorphism modulates intranasal oxytocin effects on the neural response to social cooperation in humans. (13th August 2015) - Feng, C.; Lori, A.; Waldman, I. D.; Binder, E. B.; Haroon, E.; Rilling, J. K.
<x xml:space="preserve">Abstract</x> Task design. Behavioral results. Left ventral caudate nucleus response to reciprocated cooperation (CC outcomes). <boxed-text content-type="graphic" id="gbb12234-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>